2019
DOI: 10.1038/s41598-019-54060-x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling behaviour in music and cortical dynamics interplay to mediate music listening pleasure

Abstract: The pleasure of music listening regulates daily behaviour and promotes rehabilitation in healthcare. Human behaviour emerges from the modulation of spontaneous timely coordinated neuronal networks. Too little is known about the physical properties and neurophysiological underpinnings of music to understand its perception, its health benefit and to deploy personalized or standardized music-therapy. Prior studies revealed how macroscopic neuronal and music patterns scale with frequency according to a 1/fα relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Nevertheless, Distinct roles of cognitive and sensory information in musical expectancy 30 the effect of auditory short-term memory on expectancy shown in the present work also highlights how music perception, and consequently the affective responses elicited by music, is inherently constrained by the structure of the human sensory system. This echoes the parallel between observing 1/f power-law distributions in rhythm and pitch in music across all human societies (Mehr et al, 2019) and the increased sensitivity of sensory neurons towards signals that exhibit a 1/f structure (Levitin et al, 2012), which also affects musical pleasure (Teixeira Borges et al, 2019).…”
Section: Relation To Musical Pleasurementioning
confidence: 53%
“…Nevertheless, Distinct roles of cognitive and sensory information in musical expectancy 30 the effect of auditory short-term memory on expectancy shown in the present work also highlights how music perception, and consequently the affective responses elicited by music, is inherently constrained by the structure of the human sensory system. This echoes the parallel between observing 1/f power-law distributions in rhythm and pitch in music across all human societies (Mehr et al, 2019) and the increased sensitivity of sensory neurons towards signals that exhibit a 1/f structure (Levitin et al, 2012), which also affects musical pleasure (Teixeira Borges et al, 2019).…”
Section: Relation To Musical Pleasurementioning
confidence: 53%
“…This is interesting because the same logarithmic decay has been observed in the autocorrelation function of structural brain images and characterizes both the time and space correlation at rest in human functional activity when measured with EEG, MEG or fMRI (52). The similarity between the autocorrelation function of the art piece and the functional response to it by the observer has been indicated as the potential mechanism underlying the appreciation of painters (53) with specific examples such as Jackson Pollock (54) (but see also (55) for a quantitative comparison between Pollock and van Gogh), as well as of composers, such as Bach and Mozart (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Borges et al (2018), for instance, demonstrated how the degree of scale-freeness in the brain in different frequency bands follows variations in the scale-free envelope of speech, and how their degree of correspondence impacts speech comprehension. Analogously, Borges et al (2019) show how the scale-free structures of the brain and music adapt to each other, with the brain’s neural activity somewhat rescaling the musical structure. The timing of the neuronal fluctuations, as observed in the brain’s scale-free activity, followed the timing of the fluctuations in the music (i.e., its scale-free activity), although the latter operated on a wider range of temporal scales than did the brain.…”
Section: World Brain and Self: Conceptual Implications Of The Empiric...mentioning
confidence: 97%